Promoting Photocatalytic Overall Water Splitting by Controlled Magnesium Incorporation in SrTiO3 Photocatalysts. Issue 22 (10th November 2017) - Han, Kai; Lin, Yen‐Chun; Yang, Chia‐Min; Jong, Ronald; Mul, Guido; Mei, Bastian
Abstract: SrTiO3 is a well‐known photocatalyst inducing overall water splitting when exposed to UV irradiation of wavelengths <370 nm. However, the apparent quantum efficiency of SrTiO3 is typically low, even when functionalized with nanoparticles of Pt or Ni@NiO. Here, we introduce a simple solid‐state preparation method to control the incorporation of magnesium into the perovskite structure of SrTiO3 . After deposition of Pt or Ni@NiO, the photocatalytic water‐splitting efficiency of the Mg:SrTiO x composites is up to 20 times higher compared to SrTiO3 containing similar catalytic nanoparticles, and an apparent quantum yield (AQY) of 10 % can be obtained in the wavelength range of 300–400 nm. Detailed characterization of the Mg:SrTiO x composites revealed that Mg is likely substituting the tetravalent Ti ion, leading to a favorable surface–space–charge layer. This originates from tuning of the donor density in the cubic SrTiO3 structure by Mg incorporation and enables high oxygen‐evolution rates. Nevertheless, interfacing with an appropriate hydrogen evolution catalyst is mandatory and non‐trivial to obtain high‐performance in water splitting. Abstract : Efficient tuning : The photocatalytic activity of SrTiO3 depends strongly on the donor density, which can be modified by Mg incorporation. After decreasing the donor density and modification with suitable co‐catalysts, the water‐splitting activity of Mg‐modified SrTiO x is found to be 20 times higher than of SrTiO3 .